Analisis Strategi Pemasaran Dalam Meningkatkan Penjualan Menurut Persfektif Ekonomi Islam: Studi Kasus Warung Kelontong Desa Hutarimbaru Kecamatan Barumun - Reski Khoiriah; H. Junda Harahap; Enni Efrida Nasution (Journal Economic Excellence Ibnu Sina, 2024)
Based on the results of this research, it is revealed that 1) According to the Islamic economics perspective, increasing sales at Miki Jaya grocery stalls is a strategy of product, price, place/distribution and promotion or 4P. The strategy used is in accordance with the provisions of Islamic sharia because it imitates the nature of marketing carried out by the Prophet Muhammad SAW. 2) The marketing strategy for increasing sales according to an Islamic economics perspective is using the 4Ps (product), price, place, promotion. 3) Analysis of marketing strategies for increasing sales at Miki Jaya grocery stalls Hutarimbaru Village, Barumun District, according to an Islamic economic perspective, is in accordance with the analysis carried out by researchers that the marketing strategy used by the Miki Jaya grocery store using a marketing mix strategy or 4P (product, price, place, and promotion) is in accordance with the Islamic economic perspective which uses the principles honesty, transparency in doing business so that it becomes a marketing difference between Miki Jaya grocery stalls and other stalls.